PCDD/Fs emissions from secondary copper production synergistically controlled by fabric filters and desulfurization. (1st February 2021) - Li, Haifeng; Liu, Wenbin; Lu, Anxiang; Li, Cheng; Die, Qingqi; Lei, Rongrong; Wu, Xiaolin
Abstract: The effects of fabric filters and desulfurization systems during secondary copper smelting on polychlorinated dibenzo- p -dioxins and dibenzofurans (PCDD/Fs) concentrations, emission coefficients, and profiles were studied in an oxygen-rich smelting furnace and an anode furnace. In the anode furnace, the toxic equivalent (TEQ) concentration ranges were 0.106–1.04 ng World Health Organization (WHO)-TEQ/m 3 at the fabric filters inlet and 0.027–0.17 ng WHO-TEQ/m 3 at the outlet. For the oxygen-rich smelting furnace, the TEQ concentration ranges were 1.21–1.93 and 0.010–0.019 ng WHO-TEQ/m 3 at the desulfurization system inlet and outlet, respectively. The TEQs in the outlet stack gases of the desulfurization system from the anode furnace were 0.0041–0.016 ng WHO-TEQ/m 3 . It is likely that PCDD/Fs that were taken away from the stack gases were adsorbed by the fly ash and gypsum. Solid residues were the dominant release routes for PCDD/Fs. PCDD/Fs congener and homologue profiles of stack gases from different smelting stages were similar. The contributions of more chlorinated homologues from the anode furnace decreased observably after the stack gases passed through the fabric filters. However, the desulfurization process did not greatly change the PCDD/Fs homologue profiles. Overall, both the fabric filters and desulfurization systems showed excellent removal efficiencies for PCDD/Fs in the stack gases, which reduced the TEQ emissions to well below the 0.5 ng WHO-TEQ/m 3 to achieve standard discharge. Graphical abstract: Image 1 Highlights: Effects of fabric filters and desulfurization on PCDD/Fs reduction were studied. Fabric filters and desulfurization had excellent removal efficiencies for PCDD/Fs. PCDD/F emissions from oxygen-rich smelting furnace were higher than anode furnace. The fly ash and gypsum have become new PCDD/F sources. Removal efficiencies by desulfurization decreased as chlorination level increased.